Pengaruh Pemberian Limbah Cair Tahu Terhadap Pertumbuhan Dan Hasil Produksi Pada Tanaman Selada (Lactuca sativa L.) - Widya Anggrainia; Nusyirwan (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2024)
This research was conducted at the UPT. Balai Pelaksana Penyuluhan Ketahanan Pangan Pertanian dan Perikanan (BP2KP3) located at Jl. Keramat Indah, Medan Tenggara, Medan City, North Sumatra, from March to June 2024. The study aimed to assess the effects of applying liquid tofu waste organic fertilizer (POC) on the growth and yield of lettuce plants. The research used a Randomized Block Design (RBD) with four treatments and six replications, resulting in 24 experimental plants. The treatments applied were: P0 = 0% tofu liquid waste, B = 15% tofu liquid waste (150 ml/1 liter of water), C = 30% tofu liquid waste concentration (300 ml/1 liter of water), and D = 45% tofu liquid waste concentration (450 ml/1 liter of water). The study results indicated that applying doses of tofu liquid waste influenced plant height and leaf count parameters but had no effect on leaf area and net weight of the plants. From the study, it was concluded that the optimal impact of liquid tofu waste POC on the growth and yield of lettuce plants (Lactuca sativa L.) has yet to be achieved.